Step
*
1
of Lemma
Cauchy-Schwarz-not-strict
1. n : ℕ
2. x : ℝ^n
3. y : ℝ^n
4. ¬(∃i,j:ℕn. (x j) * (y i) ≠ (x i) * (y j))
5. i : ℕn
6. j : ℕn
⊢ ((x j) * (y i)) = ((x i) * (y j))
BY
{ (BLemma `not-rneq` THEN Auto) }
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  x  :  \mBbbR{}\^{}n
3.  y  :  \mBbbR{}\^{}n
4.  \mneg{}(\mexists{}i,j:\mBbbN{}n.  (x  j)  *  (y  i)  \mneq{}  (x  i)  *  (y  j))
5.  i  :  \mBbbN{}n
6.  j  :  \mBbbN{}n
\mvdash{}  ((x  j)  *  (y  i))  =  ((x  i)  *  (y  j))
By
Latex:
(BLemma  `not-rneq`  THEN  Auto)
Home
Index